Making pulses affordable again: Policy options from the farm to retail in India - Kishore, Avinash; Joshi, Pramod Kumar; Roy, Devesh (Tata Cornell Institute, 2017)
Pulses are an important source of complex carbohydrates and the main source of noncereal protein for most Indian families. The frequency of pulse consumption is higher than of any other source of protein among Indian consumers. Around 89 percent of consumers in India have pulses at least once a week, while the corresponding number for consumption of fish, chicken, or meat is only 35.4 percent (IIPS and Macro International 2007). Pulses are also the cheapest source of non-cereal protein in India. Persistently high prices in the last few years have led to a significant decline in pulse consumption, from what was an already low level (Kumar and Joshi 2016). Rapidly rising prices of pulses have also contributed disproportionately to increases in relative prices of food (Sekhar and Bhatt 2016a). An average Indian household spends only 6–7 percent of its total food budget on pulses and pulse products, but pulses have accounted for more than 40 percent of the inflation in food prices in 2014–16 (Sekhar and Bhatt 2016a; Sekhar and Bhatt 2016b). Thus, high and rising pulse prices raise concerns for both nutrition and food price inflation. We need special policy efforts to increase the production and availability of pulses in India and make them more affordable to consumers. The central government has set the target to increase the annual production of pulses to over 24 million tonnes by 2020–21. This policy brief outlines policy strategies that can help achieve this goal, and it also points out the limitations of some of the most common recommendations for making pulses affordable in India (Kishore, Joshi, and Roy 2016).